Lao People's Democratic Republic : Staff Report for the 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
This 2013 Article IV Consultation highlights that over the past year, the economy of the Lao People's Democratic Republic has been overheating from expansionary macroeconomic policies. The fiscal deficit is estimated to have widened to 6 1\2 percent of GDP, mainly fro'm a doubling of public sector employee compensation and higher capital spending. Government liquidity is tight, and wage and other arrears of 2-3 percent of GDP have emerged. Monetary policy has been accommodative, and credit growth remains vigorous. Although medium-term growth prospects remain favorable, based on robust natural resource exports and post-WTO expansion in the nonresource sectors, heightened vulnerabilities have subjected the outlook to considerable uncertainty.